Blueberry Counteracts Prediabetes in a Hypercaloric Diet-Induced Rat Model and Rescues Hepatic Mitochondrial Bioenergetics - Nunes, Sara (2021)
The paramount importance of a healthy diet in the prevention of type 2 diabetes is now well recognized. Blueberries (BBs) have been described as attractive functional fruits for this purpose. This study aimed to elucidate the cellular and molecular mechanisms pertaining to the protective impact of blueberry juice (BJ) on prediabetes. Using a hypercaloric diet-induced prediabetic rat model, we evaluated the effects of BJ on glucose, insulin, and lipid profiles; gut microbiota composition; intestinal barrier integrity; and metabolic endotoxemia, as well as on hepatic metabolic surrogates, including several related to mitochondria bioenergetics. BJ supplementation for 14 weeks counteracted diet-evoked metabolic deregulation, improving glucose tolerance, insulin sensitivity, and hypertriglyceridemia, along with systemic and hepatic antioxidant properties, without a significant impact on the gut microbiota composition and related mechanisms. In addition, BJ treatment effectively alleviated hepatic steatosis and mitochondrial dysfunction observed in the prediabetic animals, as suggested by the amelioration of bioenergetics parameters and key targets of inflammation, insulin signaling, ketogenesis, and fatty acids oxidation. In conclusion, the beneficial metabolic impact of BJ in prediabetes may be mainly explained by the rescue of hepatic mitochondrial bioenergetics. These findings pave the way to support the use of BJ in prediabetes to prevent diabetes and its complications.